2005
DOI: 10.1073/pnas.0502655102
|View full text |Cite
|
Sign up to set email alerts
|

Physics-based protein-structure prediction using a hierarchical protocol based on the UNRES force field: Assessment in two blind tests

Abstract: Recent improvements in the protein-structure prediction method developed in our laboratory, based on the thermodynamic hypothesis, are described. The conformational space is searched extensively at the united-residue level by using our physics-based UNRES energy function and the conformational space annealing method of global optimization. The lowest-energy coarse-grained structures are then converted to an all-atom representation and energyminimized with the ECEPP͞3 force field. The procedure was assessed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
119
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 50 publications
0
119
0
Order By: Relevance
“…That the result obtained for T0663 was not a fortuitous incident is demonstrated by other good results obtained during the CASP10 exercise (Fig. 4) and in previous CASP exercises (18,19,37). It can, therefore, be concluded that our physics-based coarse-grained approach has substantial power to predict protein structures.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…That the result obtained for T0663 was not a fortuitous incident is demonstrated by other good results obtained during the CASP10 exercise (Fig. 4) and in previous CASP exercises (18,19,37). It can, therefore, be concluded that our physics-based coarse-grained approach has substantial power to predict protein structures.…”
Section: Discussionmentioning
confidence: 53%
“…Examples are, e.g., targets T0063 and T0215 of the 3rd Community Wide Experiment on the Critical Assessment of Techniques for Protein Structure Prediction (CASP3) and CASP6 experiments, respectively, whose cores are simple three α-helix bundle folds, for which threading found mirror-image folds. Conversely, correct folds were predicted by our physics-based approach based on the physics-based coarse-grained force field (United Residue, UNRES) (18,19).…”
Section: Significancementioning
confidence: 99%
“…In connection with the efficient conformational space annealing (CSA) method 50,51 of global optimization, UNRES is able to predict the structures of real-size proteins without ancillary information from structural databases. 39,43,48,49,52,53 For all these reasons, UNRES appears to be a good mezoscopic force field with which the folding pathways of proteins can be studied in real time. Therefore, our present work is aimed at implementation of the UNRES force field in a molecular dynamics algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…In the UNRES model, [17][18][19][20][21][22][23]25,27,31,32,37,38,[56][57][58] a polypeptide chain is represented by a sequence of α-carbon (C α ) atoms linked by virtual bonds with attached united side chains (SC) and united peptide groups (p). Each united peptide group is located in the middle between two consecutive α-carbons.…”
Section: The Unres Force Field For Global Optimizationmentioning
confidence: 99%
“…These conclusions were extended in our further work 27,31 to an off-lattice protein representation. Application of the hierarchical procedure using four training proteins [the LysM domain from E. coli (an α + β protein; PDB code: 1E0G 33 ), the Fbp28Ww domain from Mus musculus (a β protein; PDB code: 1E0L 34 ), the albumin-binding GA module (an α protein; PDB code: 1GAB 35 ), and the IgG-binding domain from streptococcal protein G (an α + β protein; PDB code: 1IGD 36 )] resulted in a force field capable of ab initio prediction of proteins of different structural classes with good accuracy, 32 as demonstrated further 37 in the CASP6 experiment in which we predicted complete structures of five proteins and large portions of structure of other targets.…”
Section: Introductionmentioning
confidence: 99%